Palisaded Encapsulated (Solitary Circumscribed) Neuroma of the Buccal Mucosa: a Rare Case - Saede Atarbashi-Moghadam; Ali Lotfi; Saman Salehi Zalani; Sepideh Mokhtari (Shiraz University of Medical Sciences, 2017)
The rarity of oral soft tissue spindle cell tumors combined with overlapping microscopic patterns can make challenges in their diagnosis and treatment. Oral cavity palisaded encapsulated neuroma is an uncommon lesion which occurs often on the hard palate. It is essential for oral pathologists to be familiar with its histopathology of this lesion is essential since many lesions are probably diagnosed microscopically as neurofibroma or schwannoma. Here, we report a case of oral palisaded encapsulated (solitary circumscribed) neuroma in an unusual site.